CLEC10A Is a Specific Marker for Human CD1c+ Dendritic Cells and Enhances Their Toll-Like Receptor 7/8-Induced Cytokine Secretion - Heger, Lukas; Balk, Silke; Lühr, Jennifer J.; Heidkamp, Gordon F.; Lehmann, Christian H. K.; Hatscher, Lukas; Purbojo, Ariawan; Hartmann, Arndt; Garcia-Martin, Fayna; Nishimura, Shin-Ichiro; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are major players for the induction of immune responses. Apart from plasmacytoid DCs (pDCs), human DCs can be categorized into two types of conventional DCs: CD141+ DCs (cDC1) and CD1c+ DCs (cDC2). Defining uniquely expressed surface markers on human immune cells is not only important for the identification of DC subpopulations, but is also a prerequisite for harnessing the DC subset-specific potential in immunomodulatory approaches, such as antibody-mediated antigen targeting. Although others identified CLEC9A as a specific endocytic receptor for CD141+ DCs, such a receptor for CD1c+ DCs has not been discovered, yet. By performing transcriptomic and flow cytometric analyses on human DC subpopulations from different lymphohematopoietic tissues, we identified CLEC10A (CD301, MGL) as a specific marker for human CD1c+ DCs. We further demonstrate that CLEC10A rapidly internalizes into human CD1c+ DCs upon binding of a monoclonal antibody directed against CLEC10A. The binding of a CLEC10A specific bivalent ligand (the MUC-1 peptide glycosylated with N-acetylgalactosamine) is limited to CD1c+ DCs and enhances the cytokine secretion (namely TNFα, IL-8, and IL-10) induced by TLR 7/8 stimulation. Thus, CLEC10A represents not only a candidate to better define CD1c+ DCs - due to its high endocytic potential - CLEC10A also exhibits an interesting candidate receptor for future antigen targeting approaches.